The Effectiveness Of Edmodo Application In Teaching Writing Of Procedure Text - Munawwaroh, Mina Siti Najmiyyatul; Rika Septiani (Universitas Islam Al-Ihya Kuningan, 2020)
Along with the development of the world of technology and information, learning activities are also required to change. Learning by using the internet is known as e-learning. Many applications that can be used by teachers in teaching process isEdmodo. The purpose of this study is to determine the extend to which Edmodo can improve student learning outcomes in writing text procedures and want to know what factors influence it. This study used quantitative techniques with an experimental design. The research sample consisted of 40 people who were divided into two classes (control and experiment). Data collection techniques used were questionnaires, tests and observations.The results obtained were as follows: First, the students 'scores after they were taught using the Edmodo Application were higher than before they were taught, so that means that the procedure of writing texts using the Edmodo Application is effective in improving students' writing skills. Researchers used statistical tests. From the table in SPSS 20 the computation showed the significance value (2-tailed) of this case the sample is 0.012 (p <0.05). So the results of the initial test and final test underwent significant changed. Second, there were three factors that influence why the Edmodo application can improve students' writing skills in procedure texts such as the Edmodo Application is Easy to use, Students and Teachers can enjoy in the teaching and learning process.